Industry concentration dynamics and structural changes: The case of aerospace & defence - Štefan Lyócsa; Svatopluk Svoboda; Tomáš Výrost (Charles University in Prague, Institute of Economic Studies (IES), 2010)
In this paper we present a general approach and methodology for modelling concentration dynamics on industrial level. The majority of research in this field has usually been focused on estimating adjustment models, where the speed of adjustment of actual level of concentration to the long-run concentration was considered to be responsible for concentration dynamics. The long-run concentration is usually modelled implicitly by the means of often complex industry characteristic variables. We model the changes in concentration through a) long-term structural changes in the specific industry, b) short-term structural changes, stemming from individual company conduct, and c) changes in number of companies constituting the industry. On the sample of quarterly data from 1999 to 2009 using total assets for the companies in Aerospace & Defence Industry in the U.S. we have confirmed the existence of short-term, but lacked evidence for the long-term structural changes.
Keywords: L11; D40; 330; production; pricing; market structure; size distribution of firms; Unternehmenskonzentration; Strukturwandel; Luftfahrtindustrie; Rüstungsindustrie; USA